Investigation of the expected loss of sharia credit instruments in global Islamic banks - Shahari, Farihana; Zakaria, Roza Hazli; Rahman, Md. Saifur (Emerald Group Publishing Limited, 2015)
The purpose of this paper is to investigate the expected outcomes, both of positive and negative returns occurred by shariá credit instruments in global Islamic banks. The annual panel data from 2005 to 2012 is collected from 40 Islamic banks from 12 countries and value at risk (VaR) technique is employed in the investigation process. The findings of this study indicate several outcomes: first, majority of Islamic banks use debt-based financing (DBF) and avoid asset-based financing (ABF) due to the lack of secured rate of fixed returns and collateral. Second, the ABF financing shows the positive returns. Third, interestingly, DBF financing faces higher credit risk compared to ABF even DBF secures its financing through tight policy implementation. Finally, this paper comes up with policy recommendations for the further reduction of credit risks and improvement of bankers’ confidence level in implementing the ABF financing policy.